Effect of formaldehyde to phenol molar ratio on combustion behavior of phenolic foam. (July 2022) - Tang, Kaihong; He, Xiaofeng; Xu, Guiqiu; Tang, Xiaojun; Ge, Tiejun; Zhang, Ailing
Abstract: The effects of the formaldehyde to phenol molar ratio (F/P) on the combustion behavior of phenolic foams were discussed. Phenolic foams have been prepared with different F/P of resole resin. FTIR, TG and SEM were used for assessment of the molecular structure, thermal stability, and cell structure of phenolic foam (PF) analysis, respectively. It was found that the higher the F/P, the more inflammables content in the PF that promoted the formation of the char layer, and the higher the LOI of PF. Although the closed cell proportion of PF decreases with the increase of F/P, the effect of the open and closed cell proportion on the LOI of PF was much lower than that of the content of inflammables when there was little difference in cell size. It is worth noting that the smoldering time and smoldering velocity of PF also increased with the increase of F/P. When F/P exceeds 2.3, a large number of open-cell structures appear in the PF, resulting in a phenomenon of smoldering to burnout. The relationship between smoldering velocity and F/P can be calculated by an Arrhenius type expression. Arrhenius-type expression calculation showed that when the F/P reached 2.3, the smoldering velocity increased sharply, reaching a maximum of 0.193 mm/s. Highlights: The factors affecting the combustion behavior of phenolic foam (PF) were revealed. The effect of closed cell proportion on LOI of PF is lower than that of the content of inflammables. The higher the formaldehyde to phenol molar ratio (F/P), the greater the smoldering time and velocity. The relationship between smoldering velocity and F/P can be calculated by an Arrhenius type expression.